Assessing sustainability in BRI railway projects with a novel integrated fuzzy methodology - Bouraima, Mouhamed Bayane; Dong, Simeng; Aytekin, Ahmet; Yang, Zhuanyun; Hashemkhani Zolfani, Sarfaraz; Qian, Su (Transport, 2025)
China′s Belt and Road Initiative (BRI) and South–South cooperation have received universal concern over sovereignty and debt issue, despite their goal to promote development. In Africa, the rapid expansion of Chinese-funded railway projects has overtaken the development of systematic methods for evaluating sustainability, producing a serious gap in decision-making. To address this challenge, this study proposes an integrated methodological approach, i.e., Delphi, PIvot Pairwise RElative Criteria Importance Assessment (PIPRECIA), Logarithmic Percentage Change-Driven Objective Weighting (LOPCOW), and Evaluation Based on Distance from Average Solution (EDAS) methods within the p, q Rung Orthopair Fuzzy Sets (p, q ROFSs) to assess sustainability performance under high uncertainty. The findings indicate that trade facilitation, job creation, debt sustainability, accessibility and connectivity, and safety and security are the most significant criteria for sustainability. Among the projects assessed, the Nairobi – Mombasa Standard Gauge Railway (SGR) project exhibits greatest sustainability performance, followed by the Addis Ababa – Djibouti railway while others indicated weakened outcomes because of restricted freight integration. These findings recommend that future projects should prioritize powerful trade and freight connections, guarantee employment creation and skills transfer, and implementing financing models that safeguard debt sustainability. In doing so, policymakers, managers, and planners can reinforce regional integration, improve the long-term socio-economic advantages, and obtain the operational and financial viability of extensive railway investments in Africa.